2012
DOI: 10.2522/ptj.20110280
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Measurements of Arm Joint Passive Range of Motion After Stroke: Interobserver Reliability and Sources of Variation

Abstract: Background Goniometric measurements of hemiplegic arm joints must be reliable to draw proper clinical and scientific conclusions. Previous reliability studies were cross-sectional and based on small samples. Knowledge about the contributions of sources of variation to these measurement results is lacking. Objective The aims of this study were to determine the interobserver reliability of measurements of passive range of motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…This large cohort study demonstrated very good to excellent intertester reliability when examining PROM in patients with shoulder adhesive capsulitis stage II. The results in our study are comparable or better than other reliability studies measuring shoulder ROM in normal individuals or in other shoulder populations (Table 1 ) [ 8 , 13 , 16 , 17 , 20 , 22 , 24 ]. To our knowledge this is the first reliability study that has measured passive ROM in patients with adhesive shoulder capsulitis using a plurimeter, whereas most former studies have used a variety of measuring instruments and techniques.…”
Section: Discussionsupporting
confidence: 84%
“…This large cohort study demonstrated very good to excellent intertester reliability when examining PROM in patients with shoulder adhesive capsulitis stage II. The results in our study are comparable or better than other reliability studies measuring shoulder ROM in normal individuals or in other shoulder populations (Table 1 ) [ 8 , 13 , 16 , 17 , 20 , 22 , 24 ]. To our knowledge this is the first reliability study that has measured passive ROM in patients with adhesive shoulder capsulitis using a plurimeter, whereas most former studies have used a variety of measuring instruments and techniques.…”
Section: Discussionsupporting
confidence: 84%
“…There have been many studies evaluating the validity and reliability of the UG in the clinical setting, showing good inter-rater and intra-rater reliability as well as clinical validity [2,6,9,10,11,4].…”
Section: Introductionmentioning
confidence: 99%
“…• Potential sources of measurement error include pain, oedema, dressings, joint injury, scarring, position of the person being tested, anxiety and environmental factors [61,[64][65][66][67][68]. This information suggests that, to be reliable, goniometric measurement and retesting of PROM should be performed for a particular client by the same clinician, or by clinicians trained in the same measurement protocol, with the person in the same body position each time.…”
Section: Measuring and Recording Passive Range Of Motionmentioning
confidence: 99%
“…For a change in measurement to be considered a true change in ROM (a clinically important change), the amount of change must exceed measurement error, that is, approximately 5 ∘ in the upper limb [69,70]. When recording ROM, it is essential that a consistent method be used across different clinicians in each clinical setting and where possible, across different clinical settings within which a client may receive services, to ensure reliability of measurements and allow change to be detected over time [65]. When recording ROM, it is essential that a consistent method be used across different clinicians in each clinical setting and where possible, across different clinical settings within which a client may receive services, to ensure reliability of measurements and allow change to be detected over time [65].…”
Section: Measuring and Recording Passive Range Of Motionmentioning
confidence: 99%